2014
DOI: 10.1017/s0016756813001052
|View full text |Cite
|
Sign up to set email alerts
|

A lacustrine record of the early stage of the Miocene Climatic Optimum in Central Europe from the Most Basin, Ohře (Eger) Graben, Czech Republic

Abstract: This study reports on a ß 150 m thick macrofossil-barren sequence of siliciclastic sediments from a Burdigalian age (Early Miocene) freshwater lake. The lake was located within an incipient rift system of the Most Basin in the Ohře (Eger) Graben, which was part of the European Cenozoic Rift System, and had an original area of 1000 km 2 . Sediments from the HK591 core that cover the entire thickness of the lake deposits and some of the adjacent stratigraphic units were analysed by X-ray fluorescence spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…The fact that individual element ratios reveal cycles of different order is not so surprising. A recent study of orbitally driven cyclicity in lacustrine sediments (Matys Grygar et al 2014) has shown that, e.g., Al/Si and K/Al recorded eccentricity, obliquity and precession with different sensitivity. K/Al is used as a proxy for clay mineral assemblages (see "Interpretative potential of petrophysical and geochemical proxies") and its cyclic fluctuations can be interpreted as changes in the weathering intensity and processes, which could be directly related to the original climate.…”
Section: Cyclicitymentioning
confidence: 99%
“…The fact that individual element ratios reveal cycles of different order is not so surprising. A recent study of orbitally driven cyclicity in lacustrine sediments (Matys Grygar et al 2014) has shown that, e.g., Al/Si and K/Al recorded eccentricity, obliquity and precession with different sensitivity. K/Al is used as a proxy for clay mineral assemblages (see "Interpretative potential of petrophysical and geochemical proxies") and its cyclic fluctuations can be interpreted as changes in the weathering intensity and processes, which could be directly related to the original climate.…”
Section: Cyclicitymentioning
confidence: 99%
“…Orbital forcing can also be detected in a monotonous thick marly section, showing no apparent bedding (e.g. Ghirardi et al, 2014;Matys Grygar et al, 2014). In that case, we instead suggest measuring the total thickness of the sequence several times to assess the potential dispersion of the sample steps.…”
Section: In Which Case Should This Test Be Applied?mentioning
confidence: 99%
“…Figures 2 and 3 show the major chemostratigraphic markers for the Most Basin and their lithological descriptions, which are based on several drill cores and local geochemical surveys that have been described in detail elsewhere (Matys Grygar & Mach 2013a, b;Matys Grygar et al 2014). This scheme has been used for the clastic sediments in the Bílina Mine area, which are up to 300 m thick, and in the Libouš Mine area, where they are 120 m thick.…”
Section: Chemostratigraphic Scheme For the Most Basin Clastic Sedimentsmentioning
confidence: 99%
“…The chemostratigraphic scheme that was previously published for the Libkovice Member (Matys Grygar & Mach 2013a, b;Matys Grygar et al 2014) is based on the assumption that these sediments were deposited in a single lake whose geochemistry was driven by basin-wide environmental changes. Extending that scheme to the basin periphery and to periods prior to the development of the basin-wide lake (the Holešice Member) is thus challenging because it is assumed that the basin-wide lake was preceded by several isolated water bodies .…”
Section: Upgraded Definition Of the Holeice/libkovice Boundarymentioning
confidence: 99%
See 1 more Smart Citation